From desktop to destination: User-generated content platforms, co-created online experiences, destination image and satisfaction - Lam, Jason M.S.; Ismail, Hishamuddin; Lee, Sean (Journal of destination marketing & management, 2020)
Although value co-creation concept has captured much interest, especially in the tourism and hospitality fields, limited empirical studies have been conducted to explore the complexity of experience value co-creation process in the online tourism review platform context. The current study will fill the research gap by proposing user-generated platforms as a contributor to the online co-creation process (platform engagement: pre-travel) and how this co-creation experience enhances a travel destination's image and, subsequently, impacts on the travel experience (destination engagement: at-travel). It employs a holistic model which incorporates platform-use experience, platform co-creation experience, travel destination image, and overall destination satisfaction. A total of 342 surveys were collected from travellers in Kuala Lumpur, Malaysia. Structural equation modelling analysis showed that perceived usefulness, perceived ease-of-use, aesthetics and homophily were important determinants for platform co-creation experience. Positive and significant relationships also existed between platform co-creation experience and cognitive and affective images. These images were also found to influence respondents' travel satisfaction. These findings contribute to a better theoretical understanding of the role that UGC platform use experiences play in the overall platform co-creation experience, and how this impacts on destination image formation and subsequently, satisfaction. Managerial implications, limitations and suggestions for future studies are also discussed. •UGC platforms contribute to online co-creation and destination experience.•Usefulness, ease of use, aesthetics and homophily affect platform co-creation experience.•Platform co-creation experience positively impacts on travel destination image.•Cognitive and affective image determine satisfaction at the destination.